(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
In the closed circulating water supply unit (CWW) mainly used balanced soft feed developed by factories specializing in the production of fish feed. These factories produce soft feed for a specific species. There is no natural feed base of the fishing basin in YSTQ, only artificial feeds are used to provide nutrients necessary for the development of fish. Of course, for all types of fish, the industry produces soft bait, in any case, they can be replaced if several species are close to each other according to their ecological characteristics, for example, the soft bait produced for rainbow trout can be used by other predatory fish.